Efektivitas Aplikasi Pupuk Cair Organik dari Urin Sapi Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Febi Febriani; Friza Elinda; Afrahamiryano; Muharama Yora (Fakultas Pertanian Universitas Ratu Samban, 2025)
Shallots are a horticultural crop whose production volume and harvested area have decreased. This can be overcome by administering cow urine POC because its nutrients can increase plant production. The objective of this study was to determine the impact of cow urine on onion plant growth and yield. This research was conducted from November 2023 - January 2024 in Kinari, Kec. Sundi Hill, Kab. Solok, West Sumatra with an altitude of 390 meters above sea level. A group randomized design (CRD) was used to test nine treatments arranged into three groups for this study. Four plants will be used for each treatment, totaling 108 experimental units. The treatment given is as follows, P0 = 0 ml/L, P1= 20 ml/L, P2 = 35 ml/L, P3 = 50ml/L, P4 = 65ml/L, P5 = 80ml/L, P6 = 95ml/L, P7 = 105ml/L, P8 = 120ml/L. If the F-count value of the treatment ≥the F-table value at the 95% confidence interval, then the research data analysis results will be subjected to a multiple comparison test using the Duncan New Multiple Range Test. The observation parameters observed in this study were plant height (cm), number of leaves (blade), tuber size (mm), fresh tuber yield (g), and consumption tuber yield (g) were the observational variables monitored during the study. Based on the data collected from this study are is known that the application of POC cow urine in the P3 treatment gave significantly different results in the number of tubers, tuber diameter, root volume, fresh weight of tubers, and consumption weight of tubers. There were no significant differences in the variables regarding characteristics of shoot emergence, plant height, and number of leaves.